2017
DOI: 10.1159/000479525
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Adriamycin-Induced Focal Segmental Glomerulosclerosis through C3aR/C5aR- Sphingosine Kinase 1 Pathway

Abstract: Background/Aim: Focal segmental glomerulosclerosis (FSGS) typically presents with nephrotic range proteinuria, which could eventually develop into end-stage renal disease. Resveratrol (RSV) is a natural polyphenol compound, which has been reported to suppress inflammatory response and renal interstitial fibrosis. This study is aimed at evaluating the renoprotective effect of RSV treatment on adriamycin-induced FSGS. Methods: In Balb/c mice, adriamycin nephropathy was induced by adriamycin (10 mg/kg body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In coronary artery disease, the expression of C3aR was positively correlated with activated glycoprotein IIb/IIIa in platelets, and the incidence of stroke and myocardial infarction was reduced in C3aR −/− mice (32). C3a/C3aR played a protective role in intestinal ischemia-reperfusion (IR) injury by inhibiting neutrophil mobilization (33).…”
Section: The Function Of C3a/c3ar In the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In coronary artery disease, the expression of C3aR was positively correlated with activated glycoprotein IIb/IIIa in platelets, and the incidence of stroke and myocardial infarction was reduced in C3aR −/− mice (32). C3a/C3aR played a protective role in intestinal ischemia-reperfusion (IR) injury by inhibiting neutrophil mobilization (33).…”
Section: The Function Of C3a/c3ar In the Immune Systemmentioning
confidence: 99%
“…In adriamycin (ADR)-treated mice, Liu et al found that C3aR expression was increased in the kidneys. Furthermore, it has been found that resveratrol suppressed inflammatory response, glomerulosclerosis, and renal interstitial fibrosis through down-regulation of the C3aR/C5aR-Sphk1 pathway (33).…”
Section: Focal Segmental Glomerulosclerosis (Fsgs)mentioning
confidence: 99%
“…Genes include APOL1 [9], INF2 [10], COL4A [11], MYO1E [12] and COL4A3 [13] are involved in the occurrence and development of FSGS. Signaling pathways include TGF-beta/Smad signaling pathway [14], JAK-STAT signaling pathway [15], Nrf2 signaling pathway [16], notch signaling pathway [17] and C3aR/C5aR-sphingosine kinase 1 pathway [18] plays a critical role in the pathophysiology of FSGS. Despite the increasing insights into several aspects of these mechanisms, a comprehensive overview of the integrated biological landscape underlying FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…C3aR is expressed on cell membranes in many cell types, such as epithelial cells, macrophages, T lymphocytes and dendritic cells (Reichhardt and Meri, 2018). Recent studies show that C3aR signaling is involved in various renal inflammatory dysfunctions, including diabetic kidney disease (Li et al, 2015), atypical hemolytic uremic syndrome (Sartain et al, 2018), focal segmental glomerulosclerosis (Liu et al, 2017) and immunoglobulin A nephropathy (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%